The crystal structure of tetrakis(6-phenylpyridine-2-carboxylate-κ 2 N,O)-bis(μ2-6-phenylpyridine-2-carboxylate-κ 2 O:O′)-bis(μ2-6-phenylpyridine-2-carboxylate-κ 3N,O:O)tetralead(II) C48H32N4O8Pb2 - Li-Hua Wang; Hao-Wen Tai; Qiu-Shi Li; Yu-Pei Xia; Xi-Shi Tai (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C48H32N4O8Pb2, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 9.2712(8) Å, b = 14.5959(13) Å, c = 16.6178(13) Å, α = 76.089(7)°, β = 77.068(7)°, γ = 74.717(7)°, V = 2074.5(3) Å3, Z = 2, R gt(F) = 0.0563, wR ref(F 2) = 0.1783, T = 250 K.